The Curious Case of Vodafone Idea Merger: Is It a Saga of Turbulence or a Move Towards Potence? - Chhavi Mehta; Monika Chopra
In January 2017, Vittorio Colao, the Vodafone Group CEO, and Kumar Mangalam Birla, the chairman of the Aditya Birla Group, announced a merger to form Vodafone Idea. The merger was expected to create a successful telecom company with the largest market share. Contrary to expectations, the merged entity kept struggling on various non-financial and financial business fronts. The current case discusses the motives for the merger, expected synergies, post-merger challenges and financial performance of the combined entity. The case presents the potential future strategies and a dilemma about the prospects of survival and growth of the newly created entity (3z(BVi(3y(B.s